KAJIAN STILISTIKA PADA TAJUK RENCANA SURAT KABAR HARIAN UMUM HALUAN - Syah, Nur Aini (Center of Language and Cultural Studies, 2017)
This qualitative study analyzes style used in the Haluan newspaper, emphasizing the language used in its editorials.Â The language styles were focused on the word choice, figurative language, imagery, and the role of the style.Â The data in this study were a lingual unit in the form of words, phrases, or clauses. The data sources was Editorial posted on June 6th, 2016. The results of this study showed that the use of connotative, general, special senses, and a scientific word was prominent. The figurative language, such as climax, anti-climax, repetition, redundancy, enumeration, ellipsis, polidenton, paradoxically, correction, and personification was dominant. The images contained in this Editorial included visual, motion and auditory imageries. Spiritual and social values play a role in the Haluan Daily News Editorial.Â